Peran Pendidikan Agama Kristen dalam Membimbing Pertumbuhan Kepribadian Peserta Didik - Hendro Hariyanto Siburian; Barcelina Siubelan; Marti Nuban (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Researchers found that 65% of Christian students at Inpres Batnun Elementary School had poor personalities. On average, these students carry out behavior and actions that do not reflect the personality of a disciple of Christ. This is because Christian religious education at SD Inpres Batnun does not have a visible role in guiding students. In this research, the author used a qualitative descriptive method. Researchers also conducted interviews with research subjects to obtain valid data. This research aims to look at the role of Christian religious education in guiding the personality growth of students at SD Inpres Batnun. The research results show that Christian religious educators at SD Inpres Batnun do not play a good role in guiding students' personality growth. The researchers developed strategies that could be carried out by Christian religious educators at SD Inpres Batnun to guide students' personality growth.  AbstrakPeneliti menemukan ada 65% peserta didik Kristen di Sekolah Dasar Inpres Batnun memiliki kepribadian kurang baik. Rata-rata peserta didik tersebut melakukan perilaku dan tindakan yang tidak mencerminkan pribadi murid Kristus. Hal ini disebabkan pendidikan agama Kristen di SD Inpres Batnun tidak nampak peranannya dalam pembimbing peserta didik. Dalam penelitian ini penulis menggunakan metode deskriptif kualitatif. Peneliti juga melakukan wawancara kepada subjek penelitian untuk mendapatkan data yang valid. Penelitian ini bertujuan untuk melihat peran pendidikan agama Kristen dalam membimbing pertumbuhan kepribadian peserta didik di SD Inpres Batnun. Hasil penelitian menunjukkan bahwa pendidik agama Kristen di SD Inpres Batnun tidak berperan baik dalam membimbing pertumbuhan kepribadian peserta didik. dan peneliti menyusun strategi yang dapat dilakukan oleh pendidik agama Kristen di SD Inpres Batnun dalam membimbing pertumbuhan kepribadian peserta didik.